Semantic Potential in the Legal Meanings of Revealed Texts: An Analytical Reading of Its Inference Effects within Islamic Thought - Fazry, Hamza (Journal of Islamic Sciences, 2025)
This study aims to present an analytical reading of the issue of semantic probability in the legal significations of revelation texts within Islamic thought. Its objective is to explore the true status of signification in the hierarchy of reasoning and argumentation, relying on both the descriptive-analytical method and the comparative approach in examining the various trends that address the issue. The study, across its seven sections, begins by constructing the conceptual framework of signification as a relationship between word and meaning, and between sender and receiver. It then proceeds to analyze the related problems, such as the pragmatic illusion in the classification of significations by logicians and jurists, emphasizing that semantic probability is a natural feature of all types of signification, including legal ones. The final sections are dedicated to exploring the inferential consequences of this probability, tracing the emergence of multiple levels of meaning as understood within the Islamic intellectual heritage and the debates of its scholars. The research shows that this gradation in levels of signification is intentionally established in Sharia to serve the aims of reform and ijtihad. It concludes with a core finding: although semantic probability is inherent in signification, it does not undermine the authority of revelation texts; rather, it aligns with the objectives of Sharia, which aim to activate the texts across diverse and dynamic contexts.
Keywords: Semantic Probability; Inference; Presumption; Revelation; Authoritativeness